2013
DOI: 10.1002/acr.21814
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceived cognitive dysfunction and objective neuropsychological performance in persons with rheumatoid arthritis

Abstract: OBJECTIVE Research shows a gap between perceived cognitive dysfunction and objective neuropsychological performance in persons with chronic diseases. We explored this relationship in persons with rheumatoid arthritis (RA). METHODS Individuals from a longitudinal cohort study of RA participated in a study visit that included physical, psychosocial, and biological metrics. Subjective cognitive dysfunction was assessed using the Perceived Deficits Questionnaire (PDQ; 0–20, higher scores = greater perceived impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Studies in patients with multiple sclerosis and cancer corroborated that depressive symptoms affect a patients’ report of cognitive difficulties . In RA, Shin et al found that higher levels of depression and fatigue were associated with perceived cognitive dysfunction in 120 well‐characterized patients with RA . However, we found that after adjusting for multiple other known risk factors for cognitive function, higher depression scores did not affect the development of reports of frequent concentration, memory, or word‐finding difficulties.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Studies in patients with multiple sclerosis and cancer corroborated that depressive symptoms affect a patients’ report of cognitive difficulties . In RA, Shin et al found that higher levels of depression and fatigue were associated with perceived cognitive dysfunction in 120 well‐characterized patients with RA . However, we found that after adjusting for multiple other known risk factors for cognitive function, higher depression scores did not affect the development of reports of frequent concentration, memory, or word‐finding difficulties.…”
Section: Discussionsupporting
confidence: 41%
“…In healthy cohorts, investigations of preclinical Alzheimer's type dementia have suggested that subjective cognitive complaints may precede abnormalities detected on neuropsychological testing . However, in RA, cognitive impairment can co‐occur with markers of psychological distress , and self‐reported cognitive dysfunction can be influenced by symptoms of depression and fatigue . Appreciating the role that clinical and psychological factors play in the perception of cognition is important because cognitive complaints are clinically meaningful to patients and may portend cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Because perceived cognitive impairment does not always reflect objective cognitive performance [21, 22], it is imperative to supplement cognitive function assessments that rely on self-report with more objective tests. While CAMCI® is a relatively new tool, it allows clinicians to quickly assess specific domains of cognition that patients have trouble with.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cognitive deficits in cancer patients are typically assessed using the standard paper-and-pencil tests or in-person interviews, which are time-consuming and labor intensive for patients who are already fatigued [19, 20]. Further, self- reported (or perceived) cognitive deficits do not always reflect a subject’s performance on neuropsychological (or objective) tasks [21-23]. Therefore, there is a need to develop objective cognitive tests that correspond to subjective cognitive impairments that can be useful for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, deficits in memory and attention are correlated with cognitive complaints 15,16 . In other studies of patients with immune disorders, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and multiple sclerosis, cognitive symptoms have been poorly predictive of objective performance 17,18,19 . Interestingly, despite the inconsistent relationship between cognitive complaints and objectively measured cognitive abilities, future cognitive decline has been linked to subjective cognitive complaints 20 .…”
mentioning
confidence: 99%